2014
DOI: 10.1093/eurheartj/ehu407
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of supraventricular premature complexes in community-based health checkups: The Ibaraki Prefectural Health Study

Abstract: The presence of SVPCs in 12-lead electrocardiograms was a strong predictor of AF development, and associated with increased risk of CVD in general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
60
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 29 publications
1
60
1
2
Order By: Relevance
“…In addition to demonstrating replication in our replication analyses, our findings are consistent with previous literature describing a different population: In a secondary analysis of an important recent study of over 60 000 Japanese individuals participating in annual health exams, Murakoshi et al demonstrated a greater risk of AF in those with a supraventricular premature contraction on baseline, standard resting 12‐lead ECG 26. These findings complement ours well.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to demonstrating replication in our replication analyses, our findings are consistent with previous literature describing a different population: In a secondary analysis of an important recent study of over 60 000 Japanese individuals participating in annual health exams, Murakoshi et al demonstrated a greater risk of AF in those with a supraventricular premature contraction on baseline, standard resting 12‐lead ECG 26. These findings complement ours well.…”
Section: Discussionsupporting
confidence: 92%
“…A high burden of premature atrial contractions was reduced by RDN. The herein reported study provides the first data of RDN not only on LA morphology but also on the occurrence of PAC, potentially representing triggers for AF (29,30). Because of the role of the autonomic nervous system in the pathophysiology of AF (31), the therapeutic potential of RDN in beneficially modifying atrial remodeling and thus, potentially, arrhythmogenesis has been earlier speculated (32,33 (10) and clinical (37) data also report positive effects on unstable ventricular rhythms, that is, electrical storm (38).…”
Section: Discussionmentioning
confidence: 88%
“…A Japanese cohort, the Ibaraki Prefectural Health Study, showed an 8% prevalence of PACs in the included individuals (n = 63 197). The higher prevalence of PACs may be explained by the more narrow range and older average age of the population (40–79 years), and possibly also the ethnicity of the individuals of the large‐scale database from the Ibaraki Prefectural Health Study . However, ≥1 PAC was found on 24‐hour Holter monitoring in 99% of all white, middle‐aged individuals.…”
Section: Discussionmentioning
confidence: 99%